1996
DOI: 10.1007/bf02422228
|View full text |Cite
|
Sign up to set email alerts
|

Multiple factors in the origin of the Cretaceous/Tertiary boundary: the role of environmental stress and Deccan Trap volcanism

Abstract: A review of the scenarios for the Cretaceous/ Tertiary (K/T) boundary event is presented and a coherent hypothesis for the origin of the event is formulated. Many scientists now accept that the event was caused by a meteorite impact at Chicxulub in the Yucatan Peninsula, Mexico. Our investigations show that the oceans were already stressed by the end of the Late Cretaceous as a result of the long-term drop in atmospheric CO2, the long-term drop in sea level and the frequent development of oceanic anoxia. Extin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
20
0
1

Year Published

2001
2001
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 288 publications
(255 reference statements)
1
20
0
1
Order By: Relevance
“…Glass analyses recently demonstrated that Deccan basalts were responsible for a huge HCl input into the atmosphere (4 × 10 12 g SO 2 and 1 × 10 12 g HCl released into the atmosphere per cubic kilometer of lava; Self et al, 2008b), confi rming former scenarios (Glasby and Kunzendorf, 1996). The volume of lavas extruded during Deccan phase 2 is ~80% of the total lava volume, i.e., ~10 6 km 3 (Self et al, 2006).…”
Section: Akaganeite: a New Deccan Marker?mentioning
confidence: 99%
“…Glass analyses recently demonstrated that Deccan basalts were responsible for a huge HCl input into the atmosphere (4 × 10 12 g SO 2 and 1 × 10 12 g HCl released into the atmosphere per cubic kilometer of lava; Self et al, 2008b), confi rming former scenarios (Glasby and Kunzendorf, 1996). The volume of lavas extruded during Deccan phase 2 is ~80% of the total lava volume, i.e., ~10 6 km 3 (Self et al, 2006).…”
Section: Akaganeite: a New Deccan Marker?mentioning
confidence: 99%
“…The shift to the production of smaller zooids just prior to the boundary may, however, be indicative of changes in oxygen conditions that are not driven by temperature. Anoxic events have been inferred to occur on a global scale prior to the boundary as a result of environmental perturbations from Deccan volcanism (see Glasby and Kunzendorf, 1996), and indeed the boundary clay in the Danish Basin has been suggested to represent an anoxic event (Kajiwara and Kaiho, 1992;Hart et al, 2005). What's more, alternating bioturbated and laminated chalks in other parts of the Danish basin imply the regular occurrence of dysoxic events during the Maastrichtian (Damholt and Surlyk, 2004), although no laminations were observed at Nye Kløv.…”
mentioning
confidence: 99%
“…As Deccan volcanism impacted the sedimentary record of the Cauvery basin through inducing greenhouse effect, rise in atmospheric temperature and sea level and initiation of carbonate deposition, which are recorded only at or after the end of the Cretaceous (Niniyur Formation), which in turn are much younger than the Ba anomaly. On the contrary, based on the suggestion of Hallam (1987), Glasby and Kunzendorf (1996) noted that extensive Deccan volcanism itself might have caused sea level fall by up to $100 m and sea level fall may have taken place during latest Maastrichtian. Thus, it is concluded that the impact of Deccan volcanism on sedimentation in the Cauvery basin, if any, postdates the Ba anomaly.…”
Section: Discussionmentioning
confidence: 96%
“…However, as the Ir anomalies occur in intertrappean beds, it is inferred that Deccan volcanism predates meteoritic impact (Venkatesan et al 1993;Bhandari et al 1993;Khadkikar et al 1999). In view of the enormity of Deccan volcanism (Glasby and Kunzendorf 1996) and its proximity to the study area, it could be assumed that it would have influenced the sediments of the study area more readily than the meteoritic impact in the Gulf of Mexico region. Furthermore, owing to the sampling interval of this study, lack of Ir data for the analyzed samples, the occurrence of a Ba anomaly far below the perceived K/T boundary and the occurrence of Ir anomaly at the K/T boundary, meteoritic impact and its relevance to Ba anomaly can be excluded from discussion.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation